2005
DOI: 10.1021/ja052438a
|View full text |Cite
|
Sign up to set email alerts
|

Knots in Globule and Coil Phases of a Model Polyethylene

Abstract: We examine the statistics of knots with numerical simulations of a simplified model of polyethylene. We can simulate polymers of up to 1000 monomers (each representing roughly three CH(2) groups), at a range of temperatures spanning coil (good solvent) and globule (bad solvent) phases. We quantify the abundance of knots in the globule phase and in confined polymers, and their rarity in the swollen phase. Since our polymers are open, we consider (and test) various operational definitions for knots, which are ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
223
2
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(245 citation statements)
references
References 48 publications
18
223
2
2
Order By: Relevance
“…Indeed, the analysis of protein conformations during early stages of folding clearly shows a noticeable number of randomly knotted structures. Such behavior agrees with results of simulations in (24) and well-known experimental results that flexible polymers or strings (25) can easily become spontaneously knotted. However, in most cases random knots observed in folding simulations do not lead to deep, but to relaxed knots.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, the analysis of protein conformations during early stages of folding clearly shows a noticeable number of randomly knotted structures. Such behavior agrees with results of simulations in (24) and well-known experimental results that flexible polymers or strings (25) can easily become spontaneously knotted. However, in most cases random knots observed in folding simulations do not lead to deep, but to relaxed knots.…”
Section: Discussionsupporting
confidence: 90%
“…In the case of strings and homopolymers (22,23), there are no preferred locations for nucleation of knots, and knots are equally likely to be , and N. The minimum at low Q is the unfolded ensemble, the broad minimum at Q ≈ 0.2 corresponds to the formation of the β-sheet and correct twisting, and the broad minimum at high Q is the native ensemble. The red dotted line shows the probability P K of finding a knot as a function of Q.…”
Section: Resultsmentioning
confidence: 99%
“…14 For these reasons, there is a desire to elucidate the size and probabilities of knots in polymer molecules. Accordingly, simulations addressing this issue have been performed for numerous cases: linear 6,15 and circular 16 chains, ideal 16 and selfavoiding 6 chains, flexible 6,15,16 and semiflexible 17−20 chains, lattice 17,21 and off-lattice 17,19,20 models, good 6 and bad solvents, 15,22 as well as in free space, 17,19,20 in confinement, 23−25 and under tension. 19,20 An intriguing finding from simulations is that the cores of knots very often localize at small portion of chain.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 An intriguing finding from simulations is that the cores of knots very often localize at small portion of chain. 15,16,21,23 For example, Katritch et al found the most probable size of trefoil knot on an unconfined circular ideal chain is only seven segments. 16 The localization of polymer knots has also observed in experiments, 26 and several theories have been developed to explain this behavior.…”
Section: Introductionmentioning
confidence: 99%